Rights of Victims of Sexual Violence with Disabilities Based on Law Number 12 of 2022 - Yusrotul Izza Amalia; Nur Azizah Hidayat (Indonesian Journal of Law and Policy Studies, 2022)
Sexual violence is a phenomenon of human rights violations that can occur in various countries, including Indonesia.Based on the annual disability data of the Indonesian Women's National Commission recorded in 2019 there were 89 cases and in 2020 there were 87 cases with a specific increase in sexual violence cases from 69% in 2018 to 79% in 2019. Although it does not have a variable pandemic situation, in 2020, the picture of cases of violence experienced by women with disabilities is dominated by rape. From the case of violence against women with disabilities, it is illustrated that women with intellectual disabilities are the most vulnerable group with a percentage of 47%. The purpose of this study is to find out the legal protection and rights of victims of sexual violence for persons with disabilities. This research uses normative research methods with a statutory and literature approach. The results of the study examined the rights of victims of sexual violence for persons with disabilities stipulated in Law No. 12 of 2022 concerning Sexual Violence Crimes including Special Enforcement by Law Enforcement Officials, handling procedures, protection, and recovery, state responsibility in guaranteeing the rights of persons with disabilities, and education related to public sexual violence. The regulation to protect the rights of persons with disabilities in Law No. 8 of 2016 concerning Persons with Disabilities contains: (a) The right to be free from torture, exploitation, and discrimination for persons with disabilities. (b) Interact and socialize in society, family, state, and get protection from all forms without fear of a single form